Clinical outcomes of valganciclovir prophylaxis in high‐risk (D+/R−) renal transplant recipients experiencing delayed graft function. Issue 4 (25th June 2019) - Freedman, Sari R.; Ravichandran, Bharath R.; Masters, Brian M.; Bromberg, Jonathan S.; Haririan, Abdolreza; Saharia, Kapil K.; Heil, Emily L.; Sparkes, Tracy
Abstract: Background: Cytomegalovirus (CMV) outcomes with valganciclovir prophylaxis in renal transplant recipients experiencing delayed graft function (DGF) are unclear. Methods: This single center, retrospective, cohort study of CMV high‐risk (D+/R− with alemtuzumab induction) deceased donor renal transplant recipients receiving valganciclovir prophylaxis assessed CMV outcomes in patients experiencing DGF (n = 72) versus those with immediate graft function (IGF; n = 66). Results: Cytomegalovirus viremia by 12 months occurred at similar rates in the IGF and DGF groups (30.3% vs 26.4%, respectively, P = 0.71) with 89.7% (35/39) of all cases classified as CMV disease. The median time to CMV viremia post transplant was day 141 and 138 in the IGF and DGF groups, respectively ( P = 0.30). The incidence of biopsy‐proven acute rejection (BPAR) was higher in the DGF group (18.1% vs 4.6%, P = 0.02) with BPAR preceding CMV in only 1 patient. There was no significant difference in graft loss (1.5% vs 4.2%, P = 0.62) or patient survival (98.5% vs 95.8%, P = 0.62) at 1 year between the IGF and DGF groups, respectively. Conclusion: Valganciclovir prophylaxis in patients experiencing DGF yielded similar CMV outcomes up to 1‐year post transplant when compared to use in patients with IGF.